Clinical-surgical characterization of patients with acute pancreatitis. Cienfuegos, 2018- 2020 - Jorge Luis Estepa Ramos; Tahiluma Santana Pedraza; Jorge Luis Estepa Pérez; Yudis Acea Paredes; Roberto Pérez García (Medisur)
Background: acute pancreatitis is a serious nosological entity with high morbidity and mortality. It requires systematic updating in terms of clinical and therapeutic aspects for proper management. Objective: to determine the clinical-surgical characteristics of patients with acute pancreatitis. Methods: case series research on patients admitted with a diagnosis of acute pancreatitis at the Dr. Gustavo Aldereguía Lima University General Hospital, from June the 1st, 2018 to May the 31st, 2020. Age, sex were analyzed , toxic habits, comorbidities, clinical manifestations, laboratory variables (serum amylase), ultrasonographic findings, tomographic results according to Balthazar criteria, severity index determined by computerized axial tomography, classification according to severity, place of admission, hospital stay, type of treatment , evolution and complications. Results: male patients aged 60 years old and over predominated; alcohol consumption and comorbidity not associated with acute pancreatitis, abdominal pain and vomiting were the most observed clinical variables. In most patients, serum amylase was pathological; Gallstones prevailed as an ultrasound finding; most of the patients presented mild pancreatitis. Medical treatment was the most indicated, cholecystectomy the most used surgical procedure. Most of the patients evolved satisfactorily. Conclusions: severe acute pancreatitis is a highly prevalent disease. It should be classified early with severity scales to establish adequate management that allows comprehensive treatment, from advanced support in the intensive care unit to nutritional and surgical treatment.